Load-displacement behavior of RBD palm stearin oil lubricant quantity in cold extrusion - Mohd Hafis, Sulaiman; Mohd Ridzuan, Mohd Jamir; Mohd Afendi, Rojan; Imaduddin Helmi, Wan Nordin; Boon, Raymond Whee Heng; Syahrullail, Samion, Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.